Oral health-related quality of life in children attending university special needs and paediatric dental clinics in Trinidad and Tobago: A parental perspective - Balkaran, Ramaa (United Kingdom, 2025)
Objective: To analyse the Oral Health-Related Quality of Life (OHRQoL) of 6-18-year-old children visiting the special needs and paediatric dental clinics of the University of the West Indies (UWI). Material and methods: Parents/caregivers of all 6-18-year-old children (n = 201) attending the Special Needs Dental Clinic (SNDC) and Child Dental Health Clinic (CDHC) were recruited. The Oral Health Impact Profile (OHIP-14), shortened version, was employed. Outcomes calculated were severity, prevalence, and OHIP-14 domains. Chi-square and Mann-Whitney U tests, and logistic regression models served for statistical analyses.
Results: Parents/caregivers of children with disabilities (n = 101) and without (n = 100) participated. The mean age of the children was 10.6 (3.4 standard deviation [SD]) from the SNDC and 11.3 (2.8 SD) from the CDHC. The OHRQoL differed slightly between mean severity scores for children with disabilities (6.41 ± 9.09) and without (7.01 ± 6.87) (p = 0.020). When adjusted for confounders, OHIP-14 impacts perceived occasionally, daily or very often, children with disabilities had poorer OHRQoL.
Conclusions: The overall OHRQoL among the children visiting the UWI dental clinics was poor. The OHRQoL was poorer in children with disabilities in terms of oral impacts perceived occasionally, daily or very often. Children attending for 'pain and filling' had higher odds of having OHIP-14 impact than others.